Combining Experiments and Atom Probe Tomography-Informed Simulations on γ′ Precipitation Strengthening in the Polycrystalline Ni-Base Superalloy A718Plus - Kirchmayer, Andreas; Lyu, Hao; Pröbstle, Martin; Houlle, Frederic; Förner, Andreas; Huenert, Daniela; Göken, Mathias; Felfer, Peter; Bitzek, Erik; Neumeier, Steffen (Advanced Engineering Materials, 2020)
The strength of superalloys is strongly influenced by γ′ precipitates, whose size and volume fraction which can be adjusted by heat treatments. According to classical precipitation strengthening models, an increasing precipitate diameter should lead to a transition from weak to strong coupling of the dislocation pairs that form superdislocations in the γ′ phase. We show that long-term annealing of the Ni-base superalloy A718Plus at 670 and 680 °C increases the alloy's strength without significantly changing the grain size and η fraction. To understand the effect of the slight increase in γ′ size, detailed atom probe tomography (APT) was performed. Here, different field evaporation rates of the phases strongly affect the determination of the volume fraction when using the usual isosurface construction. This can be mitigated by considering the number density of atoms inside and outside the γ′ precipitates. Using an approximation of the precipitate shapes and arrangements from the APT data in atomistic simulations revealed that precipitate shearing by both, weakly and strongly coupled dislocations can occur in the same sample due to the wide distribution of precipitate sizes. These results highlight the need for advanced strengthening models that take into account the γ′ size distribution.
CRIS-Team Scopus Importer:2020-06-02
Keywords: atom probe tomography; atomistic simulations; Ni-base superalloys; precipitation strengthening; weak–strong pair coupling

Deformation mechanisms in Ni-based superalloys at room and elevated temperatures studied by in Situ neutron diffraction and electron microscopy - Kümmel, Frank; Kirchmayer, Andreas; Solís, Cecilia; Hofmann, Michael; Neumeier, Steffen; Gilles, Ralph (Metals, 2021)
Polycrystalline Ni-based superalloys are one of the most frequently used materials for high temperature load-bearing applications due to their superior mechanical strength and chemical resistance. In this paper, we presented an in situ diffraction study on the tensile deformation behavior of the polycrystalline Ni-based superalloy VDM® Alloy 780 at temperatures up to 500 °C performed at the STRESS-SPEC neutron diffractometer at the Heinz Maier-Leibnitz Zentrum. A detailed microstructural investigation was carried out by electron microscopy before and after testing. The results of these studies allowed us to determine the deformation mechanism in the differently orientated grains. It is shown that the deformation behavior, which is mainly dislocation motion and shearing of the γ′-precipitates, does not change at this temperature range. The deformation is strongly anisotropic and depends on the grain orientation. The macroscopic hardening can mainly be attributed to plastic deformation in grains, where the (200) lattice planes were orientated perpen-dicular to the loading direction. Accordingly, a remaining lattice strain and high dislocation density were detected predominantly in these grains.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Deformation behavior; Lattice strain; Micro-structural investigation; Neutron diffraction; Ni-based superalloy; Transmission electron microscopy; kernfusionsrelevant

Influence of Grain Size and Volume Fraction of η/δ Precipitates on the Dwell Fatigue Crack Propagation Rate and Creep Resistance of the Nickel-Base Superalloy ATI 718Plus - Kirchmayer, Andreas; Pröbstle, Martin; Huenert, D.; Neumeier, Steffen; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
Recently, it was found that the orientation of the η/δ plates in the Ni-base superalloys ATI 718Plus has a huge impact on the fatigue crack propagation behavior (Huenert et al. in Superalloys pp.781–792, 2016). However, the targeted alignment of η/δ precipitates in components with complex geometry can be challenging in certain applications. Therefore, the effect of other microstructural features of ATI 718Plus, which are easier to manipulate, is tested with respect to their fatigue crack propagation behavior and creep strength. The grain size, the γ′ precipitate size, as well as the γ′ and η/δ volume fraction are varied by applying different heat treatments. An increase in the η/δ volume fraction as well as the γ′ volume fraction and precipitate size enhanced the crack growth resistance, but worsened the creep properties. On the contrary, increasing the grain size leads to better creep properties and better fatigue crack growth resistance. The impact of the different microstructures investigated in this study on the mechanical properties is smaller compared to microstructures with strongly aligned η/δ plates. These results enable to design the desired microstructures that meet the particular demands of the given application regarding crack propagation and creep resistance.
CRIS-Team Scopus Importer:2023-03-24

Influence of the γ′ Volume Fraction on the High-Temperature Strength of Single Crystalline Co–Al–W–Ta Superalloys - Xue, Fei; Bezold, Andreas; Volz, Nicklas; Kirchmayer, Andreas; Zenk, Christopher; Neumeier, Steffen; Göken, Mathias (Crystals, 2023)
Understanding the influence of γ′ and secondary-phase fractions on the mechanical properties of superalloys is very important to optimize these high-strength materials. So far, this has not been systematically investigated for the novel class of Co-based superalloys. In this study, a Co–Al–W–Ta model alloy series was designed with compositions of γ/γ′ on the tie-line and an increasing γ′ volume fraction of up to 70% after heat treatment at 900 °C, while a few alloys are unexpectedly out of γ/γ′ two-phase region with an additional secondary phase fraction of up to 15%. The high-temperature strength and creep properties were evaluated by compression tests up to 1050 °C and compressive creep experiments at 950 °C, respectively. At temperatures of up to 1050 °C, an increasing γ′ volume fraction consistently increased the yield strength, which was not dramatically changed by the presence of secondary phases. Significant work hardening was found in alloys with γ′ volume fractions of 65–70% during compression testing, but not in alloys with either a lower γ′ volume fraction (<50%) or a high fraction of secondary phases ( 15%). Similar to the yield strength, the creep strength also increased continuously with the γ′ volume fraction, but was greatly reduced with an increasing fraction of secondary phases. The best creep performance at 950 °C and 200 MPa was found in the alloy with the highest γ′ volume fraction and no secondary phases. At higher creep stresses, rafting contributed significantly to the hardening and, again, the alloy with a high γ′ volume fraction and a small amount of secondary phases exhibited the highest strength.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Co-based superalloys; compression test; creep; rafting; stacking faults; transmission electron microscopy

Investigation of the Hot Deformation Behavior in VDM® Alloy 780 by In Situ High-Energy X-Ray Diffraction - Fritton, Massimo; Kümmel, Frank; Kirchmayer, Andreas; Stark, Andreas; Hafez Haghighat, Masood; Gehrmann, Bodo; Neumeier, Steffen; Gilles, Ralph (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
Ni-based superalloys are indispensable for applications in demanding environments, such as the heavily stressed rotating discs in the hot sections of modern gas turbines or jet engines. In this paper, the microstructure evolution during hot deformation to mimic the forging process was investigated in the polycrystalline VDM® Alloy 780 viain situ X-ray diffraction at temperatures of 950, 1000, and 1050 °C. For the tested temperatures, the hot forming led to subgrain formation, the built-up of a texture by rotation of the matrix grains into preferred orientations, and dynamic recrystallization. The influence of the deformation was analyzed depending on the direction of the lattice plane normals to the load direction, for the first five γ-reflections in the diffraction pattern. During uniaxial compressive deformation intensity, maxima develop in the loading direction solely for the γ-(220) reflections, while intensity minima develop for the other reflections which correspond to the formation of a <110> fiber texture. In the transverse direction, all γ-reflections except the (220) have an increased intensity at the maximum specimen strain of 20 pct. Directly after the hot forming, three different cooling rates of 10, 100, and 1000 °C/min and their influence on the microstructure were investigated. The fast and medium cooling rates lead to low recrystallized fractions and a largely preserved deformation texture, whereas the low cooling rate leads to a high recrystallized fraction and a slight remaining texture. Additionally, the diffraction data are complemented by electron microscopy measurements.
CRIS-Team Scopus Importer:2023-01-27

Monitoring the precipitation of the hardening phase in the new VDM® Alloy 780 by in-situ high-temperature small-angle neutron scattering, neutron diffraction and complementary microscopy techniques - Solís, C.; Kirchmayer, Andreas; da Silva, I.; Kümmel, F.; Mühlbauer, S.; Beran, P.; Gehrmann, B.; Haghighat, M. Hafez; Neumeier, Steffen; Gilles, R. (Journal of Alloys and Compounds, 2022)
The hardening phase precipitation process plays an important role in the development of new Ni-base superalloys. In the present work, we apply a powerful combination of complementary characterization techniques to characterize in-situ the γ’ precipitation in the new VDM® Alloy 780. During the whole heat treatment process, in-situ time-of-flight (TOF) neutron diffraction (ND) unambiguously identified the γ’ phase as well as its weight fraction and the misfit with the matrix while in-situ small-angle neutron scattering (SANS) provided precise precipitates’ size analysis. Atom probe tomography (APT) and scanning electron microscopy (SEM) provided detailed microstructural characterization and chemical composition of the phases necessary for a proper neutron scattering data evaluation. This contribution reveals more detailed information on the nucleation, growth, and Ostwald ripening processes starting from the early precipitation stage in bulk samples using the complementary microstructure investigation methods. The nucleation and growth kinetics of precipitates at 720 °C depend on heating rates and the size distribution obtained in the pre-heating history of the sample. A subsequent heat treatment step at 620 °C, typically used in Ni-base superalloys, does not lead to similar progressive precipitation or growth. The expected matrix-diffusion-controlled Ostwald ripening process of the γ’ precipitates was in-situ monitored by SANS on a full precipitation hardened sample at expected operating temperatures (750 °C) showing slower coarsening kinetics than other reported Ni-based superalloys.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Atom probe tomography (APT); Neutron diffraction (ND); Ni-base superalloys; Ostwald ripening; Precipitation; Small-angle neutron scattering (SANS); kernfusionsrelevant

Oxidation Behavior of the Polycrystalline Ni-Base Superalloy VDM® Alloy 780 - Kirchmayer, Andreas; Weiser, Martin; Randelzhofer, Peter; Freund, Lisa; Gehrmann, B.; Haghighat, M. Hafez; Huenert, D.; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
VDM® Alloy 780 is a newly developed polycrystalline Ni-base superalloy with high contents of Co, Cr, and Al intended for operating temperatures up to 750 °C. The alloy is precipitation strengthened by the γ′ phase, which is analyzed by atom probe tomography. Additionally, δ and η phases are utilized for grain boundary pinning. It is shown that the δ and η phases precipitate either plate like or in a fine lamellar structure inside each other. VDM® Alloy 780 shows superior oxidation resistance in comparison with Udimet 720Li and A718Plus, as seen by a lower mass gain and thinner oxide layers at 800 °C and 900 °C. This superior behavior is analyzed in detail by TEM and STEM investigations of the oxide scales from which it is concluded that the Al/Ti ratio in these alloys plays an important role on the oxidation behavior.<br

The Effect of a Grain Boundary Pinning B2 Phase on Polycrystalline Co-Based Superalloys with Reduced Density - Freund, Lisa; Stark, Andreas; Kirchmayer, Andreas; Schell, Norbert; Pyczak, Florian; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2018)
The Al/W ratio was increased in a new polycrystalline gamma/gamma' Co-based superalloy in order to introduce a grain boundary pinning phase while at the same time reducing the density and increasing the oxidation resistance. The grain boundary pinning phase was identified as beta-phase (B2-(Ni,Co)Al) by high-energy X-ray diffraction. The grain boundary pinning effect was confirmed to be effective up to temperatures of 1050 degrees C by synchrotron radiation in-situ heating experiments. The precipitation of the beta phase led to a reduced gamma' volume fraction thereby decreasing the high-temperature strength. The density was lowered to 8.52 g/cm(3), so the specific strength was equivalent to the strength of the reference alloy up to 750 degrees C. Due to the low gamma' volume fraction and the low W content, the creep resistance was also reduced compared with the reference alloy. The oxidation resistance, however, was improved by the formation of a thin, continuous Al-oxide layer during oxidation at 900 degrees C for 50 hours.

The influence of crack and interface oxidation on dwell fatigue crack propagation behavior of the nickel-base superalloy ATI A718Plus - Kirchmayer, Andreas; Hausmann, Andreas; Gabel, Stefan; Pröbstle, Martin; Giese, Sven; Göken, Mathias; Hünert, Daniela; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2024)
The crack propagation properties are an important and often limiting factor for the commercial application of superalloys in aerospace applications where the oxidation ahead of the crack tip plays an important role. Previous research on the Ni-base superalloy A718Plus revealed that the orientation and the volume fraction of the high temperature grain boundary phases δ and η have a major influence on the dwell fatigue crack propagation rate at 650 °C in ambient air but not in vacuum. In this work, the effect of internal oxidation at the η/δ–matrix interface and its effect on dwell fatigue crack propagation and mechanical properties are examined by advanced microscopic methods and micro-cantilever testing. During crack propagation, the crack tip is exposed to air where a Nb-rich oxide layer forms and embrittles the η/δ–matrix interface causing the cracks to deflect and propagate along the oxidized interfaces. Micro-cantilever tests on the oxidized interface show that these oxide layers also significantly reduce the local strength and fracture toughness of the material. This proves that interfacial oxide layers are the underlying reason for the reduction of the dwell fatigue crack growth resistance at 650 °C, particularly in microstructures whose η/δ–matrix interfaces are oriented parallel to the crack growth direction.<br

The influence of crack and interface oxidation on dwell fatigue crack propagation behavior of the nickel-base superalloy ATI A718Plus - Kirchmayer, Andreas; Hausmann, Daniel; Gabel, Stefan; Pröbstle, Martin; Giese, Sven; Göken, Mathias; Hünert, Daniela; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2024)
The crack propagation properties are an important and often limiting factor for the commercial application of superalloys in aerospace applications where the oxidation ahead of the crack tip plays an important role. Previous research on the Ni-base superalloy A718Plus revealed that the orientation and the volume fraction of the high temperature grain boundary phases δ and η have a major influence on the dwell fatigue crack propagation rate at 650 °C in ambient air but not in vacuum. In this work, the effect of internal oxidation at the η/δ–matrix interface and its effect on dwell fatigue crack propagation and mechanical properties are examined by advanced microscopic methods and micro-cantilever testing. During crack propagation, the crack tip is exposed to air where a Nb-rich oxide layer forms and embrittles the η/δ–matrix interface causing the cracks to deflect and propagate along the oxidized interfaces. Micro-cantilever tests on the oxidized interface show that these oxide layers also significantly reduce the local strength and fracture toughness of the material. This proves that interfacial oxide layers are the underlying reason for the reduction of the dwell fatigue crack growth resistance at 650 °C, particularly in microstructures whose η/δ–matrix interfaces are oriented parallel to the crack growth direction.
CRIS-Team Scopus Importer:2024-02-16